The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/aem.02890-07
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput, Single-Cell Analysis of Macrophage Interactions with Fluorescently LabeledBacillus anthracisSpores

Abstract: The engulfment of Bacillus anthracis spores by macrophages is an important step in the pathogenesis of inhalational anthrax. However, from a quantitative standpoint, the magnitude to which macrophages interact with and engulf spores remains poorly understood, in part due to inherent limitations associated with commonly used assays. To analyze phagocytosis of spores by RAW264.7 macrophage-like cells in a highthroughput, nonsubjective manner, we labeled B. anthracis Sterne 7702 spores prior to infection with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 51 publications
3
26
1
Order By: Relevance
“…While most of the studies focused on late stages of bacteria-macrophage interaction [9, 35], we used the pH sensor M to monitor the early entry event of bacteria into macrophage and the bacteria-host interaction during phagocytosis process. Although the studies with B. anthracis spores suggested that a considerable percentage of spores can be killed soon after up-took into macrophage vacuoles [35-37], our study using single cell qRT-PCR suggested that bacteria are mostly intact 120 min after infection.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the studies focused on late stages of bacteria-macrophage interaction [9, 35], we used the pH sensor M to monitor the early entry event of bacteria into macrophage and the bacteria-host interaction during phagocytosis process. Although the studies with B. anthracis spores suggested that a considerable percentage of spores can be killed soon after up-took into macrophage vacuoles [35-37], our study using single cell qRT-PCR suggested that bacteria are mostly intact 120 min after infection.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate this issue, the recovery of viable, intracellular B. anthracis was compared subsequent to uptake by RAW264.7 cells in the absence or presence of FBS (10%), using the gentamicin protection assay [11,21,46,47]. These studies indicated that there were not significant differences in intracellular CFU after 5 min post-infection (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…As quality control, spore preparations were tested for both heat resistance and the capacity to germinate, as described [46]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of cell death is variable, but most cells have entered necrosis at 5 h postinfection. This variability is probably due to nonuniformity in spore intake by macrophages, which leads to heterogeneous cell killing (33).…”
Section: Resultsmentioning
confidence: 99%